Treaty Settlement Land Title and Jurisdiction: Legal and Constitutional Issues - McNeil, Kent (Osgoode Digital Commons, 2002)
This is a research report prepared for the British Columbia First Nations Summit Constitutional Issues Secretariat (21 pages).